Hybrid Control System for Greater Resilience Using Multiple Isolation and Building Connection - Taniguchi, Masaki; Fujita, Kohei; Tsuji, Masaaki; Takewaki, Izuru (Frontiers in Built Environment, 2016)
An innovative hybrid control building system of multiple isolation and connection is proposed and investigated using both time history and input energy responses for various types of ground motions together with transfer functions. It is concerned that the seismic displacement response at the base-isolation layer of the existing base-isolated buildings may extremely increase under long-period and long-duration ground motions, which are getting great attention recently. In order to enhance the seismic performance of those base-isolated buildings, a novel hybrid system of multiple isolation and building connection is proposed and compared with other structural systems such as an independent multiple isolation system, a hybrid system of base isolation and building connection. Furthermore, the robustness of seismic responses of the proposed hybrid system for various types of ground motion is discussed through the comparison of various structural systems including non-hybrid systems. Finally, the optimal connection damper location is investigated using a sensitivity-type optimization approach.